Polycarbonate copolymer solid electrolyte with sulfur-containing main chain and preparation method thereof

By using the main chain sulfur-containing polycarbonate copolymer as the solid electrolyte, the problem of low lithium ion transmission efficiency is solved, and efficient lithium ion transmission and the safety of lithium batteries are achieved.

CN119505214AActive Publication Date: 2025-02-25ZHENGZHOU UNIV

Patent Information

Application Number
CN202411840222.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-02-25
Estimated Expiration
2044-12-13

AI Technical Summary

Technical Problem

The existing solid electrolytes have low lithium ion transmission efficiency, which limits the performance and safety of lithium batteries.

Method used

The main chain sulfur-containing polycarbonate copolymer is used as the solid electrolyte, and the polymerization reaction is carried out by adding epoxide, cyclic sulfide and non-metallic catalyst to the autoclave to prepare a copolymer with excellent mechanical properties and high ionic conductivity. .

Benefits of technology

It improves the transmission efficiency of lithium ions, enhances the mechanical properties and chemical stability of electrolytes, reduces safety risks, and improves the overall performance and safety of lithium batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505214A_ABST
    Figure CN119505214A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium ion batteries, and discloses a polycarbonate copolymer solid electrolyte with a sulfur-containing main chain and a preparation method thereof. The polycarbonate copolymer with the sulfur-containing main chain is obtained by catalyzing polymerization of carbon dioxide, epoxide and episulfide by using a cheap, easily available, simple and efficient nonmetal Lewis acid and an organic amine / organic ammonium salt / organic phosphorus bi-component catalytic system, and the copolymer has excellent mechanical properties, thermal stability and chemical stability. Uniformly mixing the copolymer, a lithium salt and a plasticizer in a solvent to obtain an electrolyte solution; and preparing a membrane from the electrolyte solution on a porous support material, and carrying out vacuum drying to obtain the solid electrolyte. The room-temperature ionic conductivity of the solid electrolyte is 3.4 * 10 <-7 >-7.2 * 10 <-4 > S / cm, and the solid electrolyte has an electrochemical oxidation window of 4.5 V-5. 5V. The solid electrolyte shows excellent cycle performance and interface stability when being used for the lithium ion battery, and can effectively inhibit the growth of negative electrode lithium dendrites.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion batteries, and in particular relates to a solid electrolyte of a main chain sulfur-containing polycarbonate copolymer and a preparation method thereof. Background Art

[0002] Lithium-ion batteries are widely used in new energy vehicles and energy storage fields due to their high energy density and fast charge and discharge. Most lithium-ion batteries use traditional liquid electrolytes, which are flammable and explosive, causing a series of safety issues and greatly limiting the practical application of lithium-ion batteries. Lithium batteries using solid electrolytes have higher energy density and a wider operating temperature range, which can fundamentally solve the safety problems of lithium batteries. Therefore, solid-state lithium batteries have become an inevitable development trend of high-safety, high-performance secondary batteries.

[0003] Solid electrolytes replace traditional organic electrolytes and separators, transferring lithium ions while separating the positive and negative electrodes of the battery to prevent short circuits. Solid electrolytes are divided into inorganic solid electrolytes and polymer electrolytes. Inorganic solid electrolytes have disadvantages such as complex preparation processes, poor interface compatibility and mechanical properties, while polymer electrolytes have advantages such as good flexibility, interface compatibility and thin film formation, and are considered to be one of the ideal candidate materials for high-energy-density solid-state lithium batteries.

[0004] Commonly used polymer electrolytes, polyethylene oxide (PEO) based polymer electrolytes, have high dielectric constants and good mechanical strength and can be made into flexible electrolyte membranes, but have low ionic conductivity at room temperature.

[0005] Chinese patent CN118165249A (published on June 11, 2024) reports a poly(carbonate-ether) polyol and its preparation method. The catalyst used is Zn-Co-DMC, the chain transfer agent is a sulfhydryl compound, the monomers are epoxides and episulfides, and the dosage ratio of the four is 5mg~15mg: 0.6mmol~1.2mmol: 9mmol~70mmol: 1mmol~4mmol. After the first introduction of CO2 to the pressure in the kettle at 1MPa~2MPa, and the second introduction of CO2 to the pressure in the kettle at 3MPa~10MPa, a copolymer with a molecular weight of 850g / mol~5000g / mol is prepared; then, episulfide is used as the third monomer, and the sulfur group is introduced into the poly(carbonate-ether) polyol structure through a ternary copolymerization reaction to obtain a polycarbonate ether polyol with a molecular weight distribution index of 1.09~1.25 and a carbonate molar content of 31%~62%. However, it uses metal catalysts and has low lithium ion transmission efficiency. Summary of the invention

[0006] The purpose of the present invention is to overcome the deficiencies of the prior art and provide a main chain sulfur-containing polycarbonate copolymer solid electrolyte and a preparation method thereof, so as to solve the problem of low lithium ion transmission efficiency of the solid electrolyte in the prior art.

[0007] In order to achieve the above object, the present invention adopts the following technical solution:

[0008] A main chain sulfur-containing polycarbonate copolymer, the structure of which is shown in formula (I), wherein a, b, c≥1:

[0009]

[0010] A method for preparing a main chain sulfur-containing polycarbonate copolymer comprises the following steps: adding epoxide, episulfide and non-metal catalyst into a high-pressure reactor, introducing carbon dioxide, heating, and performing polymerization reaction, and obtaining a main chain sulfur-containing polycarbonate copolymer by precipitation and drying after the reaction. The main chain sulfur-containing polycarbonate copolymer has a molecular weight of 2000-100000 g / mol.

[0011] Preferably, in the above-mentioned method for preparing the main chain sulfur-containing polycarbonate copolymer, the non-metallic catalyst is a catalyst combining Lewis acid with one or more of organic amine, organic ammonium salt and organic phosphorus.

[0012] Preferably, in the above-mentioned method for preparing the main chain sulfur-containing polycarbonate copolymer, the Lewis acid is an organic boron compound; the organic boron compound is triethyl boron, tripropyl boron, tributyl boron, tribenzyl boron, trimethylamine boron or dimethylamine boron; the organic amine or organic ammonium salt is selected from triethylamine, tributylamine, bis(triphenylphosphorane)ammonium chloride, tetra-n-butylammonium bromide, tetra-n-butylammonium chloride, tetrabutylamine succinate, tetrabutylamine terephthalate or 1,8-diazabicyclo[5.4.0]undec-7-ene; the organic phosphorus is selected from triethyl phosphorus, triphenyl phosphorus or tetrabutyl phosphorus chloride.

[0013] Preferably, in the above-mentioned method for preparing the main chain sulfur-containing polycarbonate copolymer, the epoxide is one or more of ethylene oxide, propylene oxide, epichlorohydrin, butylene oxide, 1,2-epoxy-3,3,3-trifluoropropane, styrene oxide or epifluoropropane; the episulfide is one or more of ethylene sulfide, 2-(chloromethyl)ethylene sulfide or 2-methylethylene sulfide.

[0014] Preferably, in the above-mentioned method for preparing the main chain sulfur-containing polycarbonate copolymer, the molar ratio of the epoxide to the episulfide is 400-1900:10-500; the molar ratio of the episulfide to the organic amine or organic amine salt or organic phosphorus is 10:1-500:1; the molar ratio of the organic boron compound to the organic amine or organic amine salt or organic phosphorus is 4:1-0.5:1.

[0015] Preferably, in the above-mentioned method for preparing the main chain sulfur-containing polycarbonate copolymer, the polymerization reaction temperature is 40-100° C., the reaction pressure is 0.5-4 MPa, and the total reaction time is 3-48 hours.

[0016] A solid electrolyte of a main chain sulfur-containing polycarbonate copolymer is prepared by the following method: taking a main chain sulfur-containing polycarbonate copolymer, a lithium salt and a plasticizer, wherein the mass fraction of the lithium salt is 10%-40%, the mass fraction of the plasticizer is 0%-30%, and the balance is the main chain sulfur-containing polycarbonate copolymer; adding the three into a solvent and mixing them evenly to obtain an electrolyte solution; forming a film of the obtained electrolyte solution on a porous support material, and vacuum drying to obtain a solid electrolyte of the main chain sulfur-containing polycarbonate copolymer.

[0017] Preferably, in the solid electrolyte of the main chain sulfur-containing polycarbonate copolymer, the lithium salt is selected from one or more of lithium carbonate, lithium perchlorate, lithium hexafluorophosphate, lithium difluorophosphate, lithium bisoxalate borate, lithium difluorooxalate borate, lithium tetrafluoroborate, lithium bismalonate borate, lithium malonate oxalate borate, lithium hexafluoroarsenate, lithium trifluoromethylsulfonate, lithium bistrifluoromethanesulfonyl imide, lithium bistrifluoromethanesulfonylmethyl and lithium 4,5-dicyano-2-trifluoromethylimidazole;

[0018] The plasticizer is selected from one or more of ethanedinitrile, fluoroacetonitrile, ethylene carbonate, propylene carbonate, polyethylene glycol, γ-butyrolactone, triethyl phosphate, dimethyl carbonate, diethyl carbonate, and fluoroethylene carbonate;

[0019] The porous supporting material is any one of a porous polyimide membrane, a polyethylene terephthalate nuclear pore membrane, a cellulose nonwoven membrane, a glass fiber, a polyarylsulfone nonwoven membrane, and a polypropylene membrane.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] (1) The main innovation of the preparation method of the main chain sulfur-containing polycarbonate copolymer of the present invention is the use of a non-metallic catalyst, which is a Lewis acid and one or more component catalysts such as an organic amine / organic ammonium salt / organic phosphorus; the preparation method is obtained by a one-pot one-step process, and the copolymer has excellent mechanical properties, thermal stability and chemical stability.

[0022] (2) The preparation method of the main chain sulfur-containing polycarbonate copolymer of the present invention is simple and easy to implement, and is easy to mass produce. Carbon dioxide is used as one of the raw materials, which reduces the dependence on petroleum resources and conforms to the concept of green development.

[0023] (3) The main chain sulfur-containing polycarbonate copolymer of the present invention introduces sulfur and other polar groups into the polymer skeleton at the same time, so that the sulfur element is connected to the alkyl group, thereby enhancing the electronic insulation of the polymer and improving the ionic conductivity of the polymer. In addition, the electronegativity of -S- in the present invention is lower than that of -O-, and lithium ions can obtain a faster transmission rate in the polymer containing the sulfur main chain. In addition, the main chain sulfur-containing polymer is coated on a non-woven fabric support film such as cellulose, which can further improve the mechanical properties of the polymer electrolyte.

[0024] (4) The main chain sulfur-containing polycarbonate copolymer solid electrolyte prepared by the present invention has an ionic conductivity of 3.4×10 -7 ~7.2×10 -4 S / cm; at the same time, the solid electrolyte exhibits excellent cycle performance and interface stability when used in lithium-ion batteries, and can effectively inhibit the growth of negative electrode lithium dendrites. In addition, the solid electrolyte of the present invention does not contain flammable and explosive organic solvents, eliminating the potential safety hazard and greatly improving the safe use performance of lithium batteries. In addition, the solid electrolyte can be applied to solid-state lithium batteries (including lithium-sulfur batteries), solid-state lithium-ion batteries and other secondary high-performance lithium batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] The accompanying drawings are intended to further clearly illustrate and explain the technical solutions and embodiments of the present invention, and do not constitute a limitation of the present invention. In the accompanying drawings:

[0026] Figure 1 This is the H-NMR spectrum of the main chain sulfur-containing polycarbonate copolymer material obtained in Example 1 of the present invention.

[0027] Figure 2 This is the H-NMR spectrum of the main chain sulfur-containing polycarbonate copolymer material obtained in Example 2 of the present invention.

[0028] Figure 3 This is the H-NMR spectrum of the main chain sulfur-containing polycarbonate copolymer material obtained in Example 3 of the present invention.

[0029] Figure 4 This is a thermal decomposition curve of the main chain sulfur-containing polycarbonate copolymer material obtained in Example 1 of the present invention.

[0030] Figure 5 This is a thermal decomposition curve of the main chain sulfur-containing polycarbonate copolymer material obtained in Example 2 of the present invention.

[0031] Figure 6 This is a thermal decomposition curve of the main chain sulfur-containing polycarbonate copolymer material obtained in Example 3 of the present invention.

[0032] Figure 7This is an electrochemical impedance diagram of the main chain sulfur-containing polycarbonate copolymer electrolyte material obtained in Example 1 of the present invention tested at room temperature.

[0033] Figure 8 This is an electrochemical impedance diagram of the main chain sulfur-containing polycarbonate copolymer electrolyte material obtained in Example 2 of the present invention tested at room temperature.

[0034] Fig. 9 This is an electrochemical impedance diagram of the main chain sulfur-containing polycarbonate copolymer electrolyte material obtained in Example 3 of the present invention tested at room temperature.

[0035] Fig.10 This is a graph of the electrochemical cycle performance of the main chain sulfur-containing polycarbonate copolymer electrolyte material obtained in Example 1 of the present invention tested at room temperature. DETAILED DESCRIPTION

[0036] Example 1

[0037] In anhydrous and oxygen-free environment, 0.9g of ethylene sulfide, 13.92g of propylene oxide, 83uL of triethylamine, and 300μL of triethylborane solution were added to a 50mL high-pressure reactor in sequence, and 0.5MPa of carbon dioxide was charged. The reaction was carried out at 100℃ for 3h. After the reaction, the carbon dioxide pressure was released, and the product was dissolved with dichloromethane. The main chain sulfur-containing polycarbonate copolymer was precipitated in ethanol. The structure of the obtained copolymer is shown in formula (Ⅰ). At this time, as in formula (Ⅰ), X=CH3, Y1=H, Y2=H, a=24, b=10, and c=25. Mn=4.5kg / mol, PDI=1.7, Tg=-20℃, 30% of the main chain sulfur-containing polycarbonate copolymer, 40% of lithium bistrifluoromethanesulfonyl imide by mass fraction, and 30% of ethanedinitrile by mass fraction were stirred in acetonitrile solution overnight to form a uniform polymer electrolyte solution. The electrolyte solution is poured on the glass fiber and evaporated to form a solid polymer electrolyte membrane; the main chain sulfur-containing polycarbonate copolymer electrolyte ion conductivity is tested, and it is assembled into a battery to test the electrochemical performance. The nuclear magnetic hydrogen spectrum of the main chain sulfur-containing polycarbonate copolymer material test is as follows Figure 1 The thermal decomposition curve of the main chain sulfur-containing polycarbonate copolymer material test is shown in Figure 4 The electrochemical impedance spectroscopy of the main chain sulfur-containing polycarbonate copolymer electrolyte material tested at room temperature is shown in Figure 7 The electrochemical cycle performance of the main chain sulfur-containing polycarbonate copolymer electrolyte material tested at room temperature is shown in the figure Fig.10 shown.

[0038] Example 2

[0039] In anhydrous and oxygen-free environment, 0.65g of ethylene sulfide, 11.92g of propylene oxide, 0.03g of tetrabutylammonium chloride, and 216.00μL of triethylboron solution were added to a 50mL autoclave in sequence, and 0.5MPa of carbon dioxide was charged. The reaction was carried out at 100℃ for 3h. After the reaction, the carbon dioxide pressure was released, and the product was dissolved with dichloromethane and precipitated in ethanol to obtain a main chain sulfur-containing polycarbonate copolymer. The structure of the obtained copolymer is shown in formula (Ⅰ). At this time, as in formula (Ⅰ), X=CH3, Y1=H, Y2=H, a=57, b=3, and c=8. Mn=6.5kg / mol, PDI=1.4, Tg=25℃; 70% of the main chain sulfur-containing polycarbonate copolymer, 10% of lithium trifluoromethanesulfonate, and 20% of fluoroacetonitrile were stirred in acetonitrile solution overnight to form a uniform polymer electrolyte solution. The electrolyte solution was poured on the polyarylsulfone nonwoven membrane and evaporated to form a solid polymer electrolyte membrane. The main chain sulfur-containing polycarbonate copolymer electrolyte ion conductivity was tested, and it was assembled into a battery to test the electrochemical performance. The nuclear magnetic hydrogen spectrum of the main chain sulfur-containing polycarbonate copolymer material test is shown in Figure 2 The thermal decomposition curve of the main chain sulfur-containing polycarbonate copolymer material test is shown in Figure 5 The electrochemical impedance spectroscopy of the main chain sulfur-containing polycarbonate copolymer electrolyte material tested at room temperature is shown in Figure 8 shown.

[0040] Example 3

[0041] In anhydrous and oxygen-free environment, 1.30g of ethylene sulfide, 11.29g of propylene oxide, 60uL of triethylamine, and 432.50μL of triethylborane solution were added to a 50mL high-pressure reactor in sequence, and 1MPa of carbon dioxide was charged. The reaction was carried out at 60°C for 5h. After the reaction, the carbon dioxide pressure was released, and the product was dissolved with dichloromethane and precipitated in ethanol to obtain a main chain sulfur-containing polycarbonate copolymer. The structure of the obtained copolymer is shown in formula (I). At this time, as in formula (I), X=CH3, Y1=H, Y2=H, a=32, b=8, and c=15. Mn=4.2kg / mol, PDI=1.9, Tg=-0.5℃; 90% of the main chain sulfur-containing polycarbonate copolymer, 10% of lithium hexafluorophosphate, and 0% of gamma-butyrolactone were stirred in an acetonitrile solution overnight to form a uniform polymer electrolyte solution. The electrolyte solution was poured on the cellulose nonwoven membrane and evaporated to form a solid polymer electrolyte membrane. The main chain sulfur-containing polycarbonate copolymer electrolyte ion conductivity was tested, and it was assembled into a battery to test the electrochemical performance. The nuclear magnetic hydrogen spectrum of the main chain sulfur-containing polycarbonate copolymer material test is shown in Figure 3 The thermal decomposition curve of the main chain sulfur-containing polycarbonate copolymer material test is shown in Figure 6The electrochemical impedance spectroscopy of the main chain sulfur-containing polycarbonate copolymer electrolyte material tested at room temperature is shown in Fig. 9 shown.

[0042] Example 4

[0043] In anhydrous and oxygen-free environment, 0.87g of ethylene sulfide, 13.09g of epichlorohydrin, 0.02g of tetrabutylammonium chloride, and 216.00μL of triethylborane solution were added to a 50mL autoclave in sequence, and 1MPa of carbon dioxide was charged. The reaction was carried out at 60°C for 5h. After the reaction, the carbon dioxide pressure was released, and the product was dissolved with dichloromethane. The main chain sulfur-containing polycarbonate copolymer was precipitated in ethanol to obtain the copolymer structure as shown in formula (I). At this time, as in formula (I), X=CH2Cl, Y1=H, Y2=H, a=39, b=2, and c=15. Mn=7.0kg / mol, PDI=1.4, Tg=17°C; 60% of the main chain sulfur-containing polycarbonate copolymer, 15% of lithium difluorooxalate borate, and 25% of dimethyl carbonate were stirred in an acetonitrile solution overnight to form a uniform polymer electrolyte solution. The electrolyte solution was poured onto the polyethylene terephthalate nucleopore membrane to volatilize and form a solid polymer electrolyte membrane. The main chain sulfur-containing polycarbonate copolymer electrolyte ion conductivity was tested, and it was assembled into a battery to test the electrochemical performance.

[0044] Example 5

[0045] In anhydrous and oxygen-free environment, 0.47g 2-(chloromethyl) ethylene sulfide, 12.28g propylene oxide, 60uL triethylamine, and 864μL triethyl boron solution were added to a 50mL high-pressure reactor in sequence, filled with 4MPa carbon dioxide, reacted at 40℃ for 48h, and the carbon dioxide pressure was released after the reaction. The product was dissolved with dichloromethane and precipitated in ethanol to obtain a main chain sulfur-containing polycarbonate copolymer. The structure of the obtained copolymer is shown in formula (Ⅰ), at this time, as in formula (Ⅰ), X=CH3, Y1=H, Y2=CH2Cl, a=42, b=5, c=20. Mn=6.0kg / mol, PDI=1.9, Tg=20℃; 80% of the main chain sulfur-containing polycarbonate copolymer, 10% of lithium tetrafluoroborate, and 10% of propylene carbonate were stirred in an acetonitrile solution overnight to form a uniform polymer electrolyte solution. The electrolyte solution was cast on the cellulose nonwoven membrane and evaporated to form a solid polymer electrolyte membrane. The main chain sulfur-containing polycarbonate copolymer electrolyte ion conductivity was tested, and it was assembled into a battery to test the electrochemical performance.

[0046] Example 6

[0047] In anhydrous and oxygen-free environment, 3.24g of ethylene sulfide, 12.32g of epifluoropropane, 0.03g of tetrabutylammonium chloride, and 54.00μL of triethylborane solution were added to a 50mL autoclave in sequence, and 4MPa of carbon dioxide was charged. The reaction was carried out at 40°C for 48h. After the reaction, the carbon dioxide pressure was released, and the product was dissolved with dichloromethane. The main chain sulfur-containing polycarbonate copolymer was precipitated in ethanol. The structure of the obtained copolymer is shown in formula (I). At this time, as in formula (I), X=CH2F, Y1=H, Y2=H, a=20, b=20, and c=35. Mn=5.8kg / mol, PDI=1.5, Tg=-25°C; 60% of the main chain sulfur-containing polycarbonate copolymer, 20% of lithium bis(malonic acid borate) by mass, and 20% of triethyl phosphate by mass were stirred in an acetonitrile solution overnight to form a uniform polymer electrolyte solution. The electrolyte solution is poured on a porous polyimide separator and evaporated to form a solid polymer electrolyte membrane. The main chain sulfur-containing polycarbonate copolymer electrolyte ion conductivity is tested, and it is assembled into a battery to test the electrochemical performance.

[0048] Example 7

[0049] In anhydrous and oxygen-free environment, 0.65g of ethylene sulfide, 11.92g of propylene oxide, 0.03g of tetrabutylphosphonium chloride, and 216.00μL of triethylboron solution were added to a 50mL autoclave in sequence, and 0.5MPa of carbon dioxide was charged. The reaction was carried out at 70°C for 3h. After the reaction, the carbon dioxide pressure was released, and the product was dissolved with dichloromethane. The main chain sulfur-containing polycarbonate copolymer was precipitated in ethanol to obtain the copolymer structure as shown in formula (I). At this time, as in formula (I), X=CH3, Y1=H, Y2=H, a=48, b=5, and c=16. Mn=6.0kg / mol, PDI=1.3, Tg=20°C; 50% of the main chain sulfur-containing polycarbonate copolymer, 20% of lithium oxalate borate, and 30% of diethyl carbonate were stirred in an acetonitrile solution overnight to form a uniform polymer electrolyte solution. The electrolyte solution is poured on the glass fiber membrane and evaporated to form a solid polymer electrolyte membrane. The main chain sulfur-containing polycarbonate copolymer electrolyte ion conductivity is tested, and it is assembled into a battery to test the electrochemical performance.

[0050] Example 8

[0051] In anhydrous and oxygen-free environment, 0.87g of ethylene sulfide, 13.09g of epichlorohydrin, 0.02g of tetrabutylammonium chloride, and 432.00μL of triethylphosphine solution were added to a 50mL autoclave in sequence, and 1MPa of carbon dioxide was charged. The reaction was carried out at 60°C for 5h. After the reaction, the carbon dioxide pressure was released, and the product was dissolved with dichloromethane. The main chain sulfur-containing polycarbonate copolymer was precipitated in ethanol to obtain the copolymer structure as shown in formula (I). At this time, as in formula (I), X=CH2Cl, Y1=H, Y2=H, a=30, b=5, and c=5. Mn=5.3kg / mol, PDI=1.25, Tg=30°C; 40% of the main chain sulfur-containing polycarbonate copolymer, 30% of bistrifluoromethanesulfonylmethyl lithium, and 30% of fluoroethylene carbonate were stirred in an acetonitrile solution overnight to form a uniform polymer electrolyte solution. The electrolyte solution was cast on a polypropylene film and evaporated to form a solid polymer electrolyte membrane. The main chain sulfur-containing polycarbonate copolymer electrolyte ion conductivity was tested, and it was assembled into a battery to test the electrochemical performance.

[0052] Table 1. Ionic conductivity at room temperature and at 60°C

[0053] name Room temperature conductivity Conductivity at 60℃ Example 1 3.90E-04 7.20E-04 Example 2 8.60E-06 1.82E-05 Example 3 3.40E-07 2.62E-06 Example 4 3.65E-05 1.68E-04 Example 5 6.30E-06 3.62E-05 Example 6 2.16E-04 3.28E-04 Example 7 3.24E-04 4.46E-04 Example 8 3.58E-04 5.63E-04

[0054] pass Figure 1-10 As well as the data in Table 1, it is shown that the main chain sulfur-containing polycarbonate copolymer was successfully synthesized using non-metallic catalysis, and the copolymer has a high thermal decomposition temperature; the copolymer is applied to solid electrolytes and solid-state lithium-ion batteries to have high ionic conductivity and cycle performance.

Claims

1. A main chain sulfur-containing polycarbonate copolymer, the structure of which is shown in formula (I), wherein a, b, c ≥ 1: X=H or CH3 or CF3 or CH2Cl or CH2F or CH2CH3 or CH2C8F 17 Y1=H or CH2Cl or CH3, Y2=H or CH3 (I)。 2. A method for preparing the main chain sulfur-containing polycarbonate copolymer according to claim 1, characterized in that The method comprises the following steps: adding epoxide, episulfide and non-metal catalyst into a high-pressure reactor, introducing carbon dioxide, heating, and performing polymerization reaction; and obtaining a main-chain sulfur-containing polycarbonate copolymer by precipitation and drying after the reaction.

3. The method for preparing a main chain sulfur-containing polycarbonate copolymer according to claim 2, characterized in that: The non-metal catalyst is a catalyst formed by combining Lewis acid with one or more of organic amine, organic ammonium salt and organic phosphorus.

4. The method for preparing a main chain sulfur-containing polycarbonate copolymer according to claim 3, characterized in that: The Lewis acid is an organic boron compound; the organic amine or organic ammonium salt is selected from triethylamine, tributylamine, bis(triphenylphosphorane)ammonium chloride, tetra-n-butylammonium bromide, tetra-n-butylammonium chloride, tetrabutylamine succinate, tetrabutylamine terephthalate or 1,8-diazabicyclo[5.4.0]undec-7-ene; and the organic phosphorus is selected from triethylphosphine, triphenylphosphine or tetrabutylphosphine chloride.

5. The method for preparing a main chain sulfur-containing polycarbonate copolymer according to claim 2, characterized in that: The epoxide is one or more of ethylene oxide, propylene oxide, epichlorohydrin, butylene oxide, 1,2-epoxy-3,3,3-trifluoropropane, styrene oxide or epifluoropropane; the episulfide is one or more of ethylene sulfide, 2-(chloromethyl)ethylene sulfide or 2-methylethylene sulfide.

6. The method for preparing a main chain sulfur-containing polycarbonate copolymer according to claim 2, characterized in that: The molar ratio of the epoxide to the episulfide is 400-1900:10-500; the molar ratio of the episulfide to the organic amine or organic amine salt or organic phosphorus is 10:1-500:1; the molar ratio of the organic boron compound to the organic amine or organic amine salt or organic phosphorus is 4:1-0.5:

1.

7. The method for preparing a main chain sulfur-containing polycarbonate copolymer according to claim 2, characterized in that: The polymerization reaction temperature is 40-100° C., the reaction pressure is 0.5-4 MPa, and the total reaction time is 3-48 hours.

8. A solid electrolyte of a main chain sulfur-containing polycarbonate copolymer, characterized in that The method is prepared by the following method: taking a main chain sulfur-containing polycarbonate copolymer, a lithium salt and a plasticizer, wherein the mass fraction of the lithium salt is 10%-40%, the mass fraction of the plasticizer is 0%-30%, and the balance is the main chain sulfur-containing polycarbonate copolymer; adding the three into a solvent and mixing them evenly to obtain an electrolyte solution; forming a film of the obtained electrolyte solution on a porous support material, and vacuum drying to obtain a solid electrolyte of the main chain sulfur-containing polycarbonate copolymer.

9. The solid electrolyte of the main chain sulfur-containing polycarbonate copolymer according to claim 8, characterized in that: The lithium salt is selected from one or more of lithium carbonate, lithium perchlorate, lithium hexafluorophosphate, lithium difluorophosphate, lithium bisoxalatoborate, lithium difluorooxalatoborate, lithium tetrafluoroborate, lithium bismalonateborate, lithium oxalatoborate, lithium hexafluoroarsenate, lithium trifluoromethylsulfonate, lithium bistrifluoromethanesulfonyl imide, lithium bistrifluoromethanesulfonylmethyl and lithium 4,5-dicyano-2-trifluoromethylimidazole; The plasticizer is selected from one or more of ethanedinitrile, fluoroacetonitrile, ethylene carbonate, propylene carbonate, polyethylene glycol, γ-butyrolactone, triethyl phosphate, dimethyl carbonate, diethyl carbonate, and fluoroethylene carbonate; The porous supporting material is one of a porous polyimide membrane, a polyethylene terephthalate nuclear pore membrane, a cellulose nonwoven membrane, a glass fiber, a polyarylsulfone nonwoven membrane, and a polypropylene membrane.

10. A solid-state lithium battery, characterized in that A solid electrolyte comprising the main chain sulfur-containing polycarbonate copolymer according to claim 8.

Citation Information

Patent Citations

  • Phosphorus salt organic boron catalyst as well as preparation method and application thereof

    CN115710288A

  • Carbon dioxide-based terpolymer electrolyte as well as preparation method and application thereof

    CN116053575A

  • Poly (carbonate-ether) polyol and preparation method thereof

    CN118165249A

  • Method for producing cyclic trithiocarbonate

    JP2012214386A

  • Catalyst for cyclic carbonate synthesis, and method for synthesizing cyclic carbonate

    JP2013063417A

Cited By

  • Structural battery electrolyte with excellent impact resistance and preparation method and application thereof

    CN121097180A

  • Structural battery electrolyte with excellent impact resistance and preparation method and application thereof

    CN121097180B